Os incentivos fiscais como determinantes da localização das empresas multinacionais de alta tecnologia - Rohde, Elisa dos Passos Costa (2013)
This paper empirically analyzed the role of tax incentives in the location decisions of one hundred high-tech multinationals invest more in research and development (R & D) in 2010. Many factors can influence them according to the literature regarding: economic and institutional environments stable show up essential, however, some locations are more attractive than others, suggesting that guaranteed the fundamental elements, there are other factors that determine the choice from one location. In this study, the hypothesis is that the practice of lower tax levels generated by tax incentives positively influence the locational decisions of high-tech companies. This hypothesis is confirmed by empirical results that relate positively to choose the location of high-tech companies with low taxes.